Trends in HPV Vaccine Initiation and Completion among Girls in Texas: Behavioral Risk Factor Surveillance System Data, 2008–2010 - Gazibara, Tatjana; Jia, Haomiao; Lubetkin, Erica I. (Puerto Rico Health Sciences Journal, 2017)
Objective: The objective of this study was to evaluate the trend of HPV vaccine initiation and completion among girls in Texas from 2008 to 2010. Methods: Data were obtained from the Behavioral Risk Factors Surveillance System (BRFSS) over 3 years (2008–2010). The information regarding HPV vaccination was gathered from the parents of 9- to 17-year-old daughters (choosing only 1 per household) in randomly selected households in the sample area. Results: The highest prevalence of vaccine initiation and completion were detected in 2010 (20.9% and 9.7%, respectively). Over the study period, HPV vaccine initiation statistically significantly increased (2008, 14.9%; 2009, 20.7%; 2010, 24.3%; p = 0.002), corresponding to an annual increase in coverage of 33.5% (odds ratio [OR] = 1.33; 95% confidence interval [CI]: 1.11–1.60). Similarly, HPV vaccination completion increased (2008, 6.3%; 2009, 9.6%; 2010, 11.6%; p = 0.021), corresponding to an annual increase in coverage of 37.1% (OR = 1.37; 95% CI: 1.05–1.79). Increasing trends in HPV vaccination initiation and completion were observed in mothers, white, non-Hispanic parents, parents who had attended some college or were college graduates, parents who were married/partnered, and parents who lived in urban areas. Conclusion: Although HPV vaccination coverage in Texas is lower than recommended, there have been increases in the trends of vaccine initiation and completion. The campaigns promoting HPV vaccination should target specific population groups in which HPV immunization rates did not increase over time.